Effect of inferior alveolar plus buccal nerve block on donor site morbidity at buccal mucosal graft harvest site: A double-blinded, randomized placebo-controlled trial - Vivek Tarigopula; Swarnendu Mandal; Gorrepati Rohith; Dheeraj Kumar Dheeroo; Manoj Kumar Das; Sambit Tripathy; Kalandi Barik; Prasant Nayak (Indian Journal of Urology)
Introduction: Pain at the buccal mucosal graft (BMG) harvest site in the immediate postoperative period is common and delays resumption of oral intake. This study compares the time for resumption of pain-free solid and liquid diets and postoperative pain scores at harvest site following the administration of inferior-alveolar nerve-block plus buccal-nerve block (IANB + BNB) versus placebo. We hypothesize that the intervention could decrease pain and aid in early food intake. Methods: A single-center, placebo-controlled, double-blinded randomized-control trial was conducted from September 2022 to August 2023 (CTRI). All individuals > 18 years undergoing BMG harvest were included. Patients with contraindications for BMG harvest and diabetes were excluded. Furthermore, patients requiring additional lingual/labial graft, bilateral BMG, or a history of prior BMG harvest were also excluded. IANB + BNB was performed with a 10 ml mixture comprising lignocaine, bupivacaine, and dexamethasone, while normal saline was administered in the control group. Both groups received submucosal local anesthetic infiltration. Results: After randomization (n = 28 in each group), patients who received IANB + BNB had an early return to pain-free liquid (median 1 vs. 2 days; P ≤ 0.001) and solid diet (median 2 vs. 3 days; P = 0.001) 1 day quicker than those who received placebo. In the intervention arm, Visual Analog Scale scores at harvest site were lower from 2 to 48 h postoperatively, had reduced paracetamol requirement (median 7 g vs. 9 g; P = 0.001), and fewer necessitated opioids for breakthrough pain (14.4% vs. 53.3%; P = 0.002). Conclusion: Patients who received IANB + BNB resumed a pain-free diet in the postoperative period quicker, reported lower pain scores, and there were lesser postoperative analgesic requirements.